2020
DOI: 10.1002/adfm.202003635
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Nonvolatile Memcapacitance in Graphene‐Silk Fibroin Biocomposite Paper

Abstract: The demand for flexible memory devices is growing due to the development of flexible neuromorphic electronics for wearable devices, soft robotics, and biologically-inspired circuits. Described herein is a flexible memcapacitor based on a biocomposite paper composed of reduced graphene oxide (rGO) and silk fibroin (SF) via a gel-film transformation process. The presented rGO-SF/H 3 PO 4-polyvinyl alcohol (PVA)/rGO memory stack exhibits analog, reversible, and nonvolatile memcapacitance characteristics. Impressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The existence of a large memcapacitive effect is confirmed by measuring the remanent -overall-device capacitance C REM after the application of voltage write pulses between 0 and 1 V (small enough to avoid triggering a RESET transition). These measurements are shown in Figure 3(e) and display a C HIGH /C LOW ratio of ≈ 100, that is an order of magnitude higher than the figures reported so far [25][26][27][28][29][30][31][32][33]. We notice that C REM is a function of the equivalent circuit elements (Table 1) and the frequency ω, as described by the Maxwell-Wagner model [36].…”
Section: Characterization Of Voltage-controlled Devicesmentioning
confidence: 59%
See 1 more Smart Citation
“…The existence of a large memcapacitive effect is confirmed by measuring the remanent -overall-device capacitance C REM after the application of voltage write pulses between 0 and 1 V (small enough to avoid triggering a RESET transition). These measurements are shown in Figure 3(e) and display a C HIGH /C LOW ratio of ≈ 100, that is an order of magnitude higher than the figures reported so far [25][26][27][28][29][30][31][32][33]. We notice that C REM is a function of the equivalent circuit elements (Table 1) and the frequency ω, as described by the Maxwell-Wagner model [36].…”
Section: Characterization Of Voltage-controlled Devicesmentioning
confidence: 59%
“…A very interesting topotactic redox perovskite is La 1/2 Sr 1/2 Mn 1/2 Co 1/2 O 3−x (LSMCO), which displays and oxidized -more conducting-phase with x = 0 and a rhomboedral R 3c structure, as well as a reduced -more resistive-phase with x =0.62 and an orthorombic Pbnm structure [23]. We have shown [24] that epitaxial Nb:SrTiO 3 /LSMCO structures display a robust memristive behavior concomitant with a memcapacitive effect -reversible change in the capacitance between different non-volatile states [25][26][27][28][29][30][31][32][33]-. The memcapacitance found in this system -C HIGH /C LOW ≈ 900 at 10 kHz and ≈ 100 at 150 kHz-was the highest reported to date by a factor of ≈ 10 and originates at the NSTO/LSMCO interface, where a switchable p-n diode is formed [24].…”
Section: Introductionmentioning
confidence: 93%
“…[ 7 ] Guo et al reported a capacitance change in a reduced graphene oxide‐silk fibroin/H 3 PO 4 –poly(vinyl alcohol)/reduced graphene oxide stack resulting from interfacial charging by H + migration. [ 8 ] The capacitance change due to charge trapping/detrapping induced Schottky barrier modulation was also reported in the Au/LaSrNiO 4 /Au structure by Zhao et al [ 9 ] We previously reported that the C ox in a Pt/HfO x /n‐type indium–gallium–zinc–oxide(IGZO) capacitor changed upon applying a gate bias owing to the oxygen ion migration between HfO x and IGZO. [ 10 ] In addition, C ox modulation was also identified in the indium‐tin‐oxide(ITO)/HfO x /Si [ 11 ] and ITO/CeO 2 /Si [ 12 ] capacitors owing to the oxygen ion migration between the ITO gate electrode and the HfO x and CeO 2 layers.…”
Section: Introductionmentioning
confidence: 71%
“…OPDs with large LDR values can lead to conversion of both strong and weak light signals to electrical signals. [ 37 ] As shown in Figure 5c, the LDR varying from 1‐Sun (100 mW cm −2 ) to the dark condition was calculated for the 330 nm (pristine) and 330 nm (1‐CN) devices with applied biases of −0.1 V. The LDR was calculated according to the following equation LDRbadbreak=20goodbreak×logJupperJlower\[ \begin{array}{*{20}{c}}{{\rm{LDR}} = 20 \times \log \frac{{{J_{{\rm{upper}}}}}}{{{J_{{\rm{lower}}}}}}}\end{array} \] where J upper is the maximum value of the photocurrent density, and J lower is the minimum value of the dark current density. The 330 nm (pristine) device showed an LDR value of 105 dB, whereas the 330 nm (1‐CN) device showed an improved LDR value of 122 dB based on the relatively higher J upper (9.11 × 10 −3 A cm −2 ) and suppressed J lower (7.14 × 10 −9 A cm −2 ).…”
Section: Resultsmentioning
confidence: 99%